Pacita Abad - Sung, Victoria 1987-; Sung, Victoria 1987-; Abad, Pio 1983-; Bryan-Wilson, Julia 1973-; Katrib, Ruba 1982- (Walker Art Center, 2023)
"Catalogue surveying three decades of contemporary Filipina American artist Pacita Abad's multifaceted practice. Published in conjunction with the artist's first retrospective exhibition Pacita Abad, the catalogue includes new essays by Julia Bryan-Wilson, Ruba Katrib, Nancy Lim, Victoria Sung, Xiaoyu Weng, and a narrative oral history edited by Pio Abad and Victoria Sung"--